(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The performance evaluation had Focused for many years ago on The financial factors which are Not enough for the contemporary business organizations. So in order to get useful information it con used The balanced score card which can used to offer information about some measurement on which the level of the act actual performance is determined.